Diversification of the climatic niche drove the recent processes of speciation in Sigmodontinae (Rodentia, Cricetidae). (11th July 2018) - Reis, Jennifer; Bidau, Claudio J.; Maestri, Renan; Martinez, Pablo A.
Abstract: Evolutionary radiations are among the most intriguing natural phenomena. Sigmodontine rodents form a megadiverse group for which doubts exist about the adaptive or non‐adaptive nature of its radiation. We analysed whether or not the rates of diversification of species of Sigmodontinae are related to the rates of diversification of the climatic niches occupied by the species. Our results show a clear association between niche diversification and speciation processes. However, this association is linked to recent and independent processes of diversification in sigmodontines, as opposed to an early link that would indicate a niche‐filling consistent with an adaptive radiation of the subfamily.